2019
DOI: 10.1104/pp.19.00532
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Target Mapping Shows Histone Deacetylase Complex1 Regulates Cell Proliferation in Cucumber Fruit

Abstract: Histone deacetylase (HDAC) proteins participate in diverse and tissue-specific developmental processes by forming various corepressor complexes with different regulatory subunits. An important HDAC machinery hub, the Histone Deacetylase Complex1 (HDC1) protein, participates in multiple protein-protein interactions and regulates organ size in plants. However, the mechanistic basis for this regulation remains unclear. Here, we identified a cucumber (Cucumis sativus) short-fruit mutant (sf2) with a phenotype that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 89 publications
2
42
0
Order By: Relevance
“…Some studies have shown that exogenous treatment of the −3 DAA female flowers with thidiazuron (N-phenyl-N -1,2,3-thiadiazol-5-yl urea, TDZ), an inhibitor of CKX (cytokinin oxidase), partially complemented the short fruit phenotype, and the treatment had a much stronger effect on the sf2 mutant than on WT fruit. This is consistent with a role for SF2 in facilitating cell proliferation through modulation of CK contents [43]. Intriguingly, the ZT concentration was also relatively higher before anthesis and showed a sharp increase in the exponential growth stage (6 to 12 DAA), especially the inbred lines with wider fruit diameters.…”
Section: Discussionsupporting
confidence: 85%
“…Some studies have shown that exogenous treatment of the −3 DAA female flowers with thidiazuron (N-phenyl-N -1,2,3-thiadiazol-5-yl urea, TDZ), an inhibitor of CKX (cytokinin oxidase), partially complemented the short fruit phenotype, and the treatment had a much stronger effect on the sf2 mutant than on WT fruit. This is consistent with a role for SF2 in facilitating cell proliferation through modulation of CK contents [43]. Intriguingly, the ZT concentration was also relatively higher before anthesis and showed a sharp increase in the exponential growth stage (6 to 12 DAA), especially the inbred lines with wider fruit diameters.…”
Section: Discussionsupporting
confidence: 85%
“…Beyond ARFs, which act as key upstream regulators during auxin signaling, another area of focus is the characterization of downstream auxin‐responsive genes affecting cell division. Among these are genes encoding ATP‐binding cassette transporters (ABCBs), members of the GRAS family, and proteins that function in the histone de‐acetylase (HDAC) machinery (Huang et al ., 2017; Ofori et al ., 2018; Zhang et al ., 2020b). It is possible that ABCBs function during early fruit growth in tomato to transport and distribute auxin during cell proliferation, as cell division in tomato occurs within 1–2 weeks of pollination, depending on the genotype, and it was observed that expression of SlABCB4 peaks around 14 DAP.…”
Section: Fruit Growth (Cell Division and Expansion)mentioning
confidence: 99%
“…The SF2 locus encodes a homolog of AtHDC1 in cucumber that functions as an important component of the HDAC complex, and its expression is highest in meristematic tissues that experience elevated rates of cell division. SF2 specifically targets and represses genes that suppress responses to auxin, GA, and CK signaling, and cell division rates were significantly decreased in sf2 mutants (Zhang et al ., 2020b). These recent observations regarding the intersection of hormonal pathways and epigenome modifications in the regulation of fruit cell division and growth present an exciting opportunity to peel back an additional layer of regulatory control in this process.…”
Section: Fruit Growth (Cell Division and Expansion)mentioning
confidence: 99%
“…S1) 19 . And 18,16,19,14,19,17 and 11 InDel markers were located on chromosome 1 to chromosome 7, respectively ( Supplementary Fig. S1).…”
Section: Molecular Marker Developmentmentioning
confidence: 99%